From CNTNAP2 to Early Expressive Language in Infancy: The Mediation Role of Rapid Auditory Processing. (11th May 2017) - Riva, Valentina; Cantiani, Chiara; Benasich, April A; Molteni, Massimo; Piazza, Caterina; Giorda, Roberto; Dionne, Ginette; Marino, Cecilia
Abstract: Although it is clear that early language acquisition can be a target of CNTNAP2, the pathway between gene and language is still largely unknown. This research focused on the mediation role of rapid auditory processing (RAP). We tested RAP at 6 months of age by the use of event-related potentials, as a mediator between common variants of the CNTNAP2 gene (rs7794745 and rs2710102) and 20-month-old language outcome in a prospective longitudinal study of 96 Italian infants. The mediation model examines the hypothesis that language outcome is explained by a sequence of effects involving RAP and CNTNAP2 . The ability to discriminate spectrotemporally complex auditory frequency changes at 6 months of age mediates the contribution of rs2710102 to expressive vocabulary at 20 months. The indirect effect revealed that rs2710102 C/C was associated with lower P3 amplitude in the right hemisphere, which, in turn, predicted poorer expressive vocabulary at 20 months of age. These findings add to a growing body of literature implicating RAP as a viable marker in genetic studies of language development. The results demonstrate a potential developmental cascade of effects, whereby CNTNAP2 drives RAP functioning that, in turn, contributes to early expressive outcome.